Geometria diferencial da cuspidal edge - Paniche, Beatriz Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Seja M a superfície cuspidal edge, a qual é uma superfície de posto 1 parametrizada por uma frente de onda. Neste trabalho estudamos invariantes geométricos que determinam M, como a curvatura umbílica para superfícies de posto 1, as curvaturas singular, normal e cuspidal para frentes de onda e a curvatura inflexional e torção cuspidal. Além disso, esclarecemos as relações entre estes invariantes geométricos.

Let M be a cuspidal edge which is a corank 1 surface given by a wave front. In this work we study geometric invariants that determine M, such as the umbilic curvature for surfaces with corank 1 singularities, the singular, normal and cuspidal curvatures for wave fronts and the inflexional curvature and cuspidal torsion. In addition, we clarify the relationships between these geometric invariants.
Differential geometry of cuspidal edge
Keywords: Superfícies singulares; Cuspidal egde; Geometria diferencial; Frentes de onda; Singular surfaces; Diferencial geometry; Wave fronts